Studies on the dielectric behavior in (tOO-x) wt, % methyl cellulose (MC) +x wt. % NH4N03 polymer electrolytes - Shuhaimi, N.E.A.; Majid, S.R.; Arof, Abdul Kariem (2009)
This paper reports the dielectric behavior of (IOO-x)MC + x NH4N03 (x=5, 10, 15, 20,25 and 30 wt. %) electrolyte system calculated using data from impedance measurement at room temperature over the frequency range 50 Hz to 1 M Hz. The results obtained show that dielectric constant, dielectric loss, imaginary part of electrical modulus and loss tangent shows changes with frequency. The dielectric properties of the samples at low frequenecies have been explained on the basis of space charge polarization. The relaxation time for the samples is determined from the variation of loss tangent at different frequencies at room temperature. The relaxation time decreases with conductivity of the complexes.